METODE DAN PERTIMBANGAN UNTUK MELEPAS RESTORASI CEKAT SECARA KONSERVATIF - Eri H. Jubhari (Journal of Dentomaxillofacial Science, 2002)
A fixed restoration should be removed because it hasdistortions at the restoration or its abutment. It's not an easyprocess, especially when it has been cemented permanently. Todo so, it is necessary to know the restoration history, cement,abutment, "' and the method. Some methods for removing thefixed restoration intactly are follow: straight chisel and mallet,excavator, reverse mallet, ATD, peerless crown-a-matic,adhesive method, ligature, Reynold technique andforcep.Altough physical and psychological traumas during the removingprocess have been prevented, dentist must give adequateinformed concent, take care the abutment health and prevent thepatient from swallowing the restoration.